Quality of Life in Chinese Patients With Large Congenital Melanocytic Nevi - Wang, Huijing; Yu, Qingxiong; Li, Qingfeng; Wang, Zhichao (Frontiers in Pediatrics, 2022)
Background: Large congenital melanocytic nevus (LCMN) is a rare skin disease that deeply affects an individual’s appearance, may influence patients’ self-evaluation and social relationships, and further affects their quality of life (QoL). The Skindex-29 and 36-Item Short Form Survey (SF-36) are valid instruments used to evaluate QoL specifically. It is necessary to assess the QoL of patients with LCMN and summarize potentially impactful factors to help people understand LCMN patients and assist doctors in offering professional advice. Methods: Twenty-five patients were recruited from Shanghai Ninth People’s Hospital from July 1st, 2019, to March 31st, 2021. Both males and females were included, and the age groups were divided into infants (0-6 y), children (7-12 y), teenagers (13-17 y) and youths (18-45 y). The Skindex-29 and SF-36 were applied as questionnaires for the assessment of QoL. Clinical information was acquired by physical examination. Results: QoL in patients with LCMN was diminished, especially in the emotional aspect. However, different genders, ages and distribution patterns of LCMN did not significantly influence QoL, but the patterns of “Bonce” and “Body” affected QoL the most and the severest. The results of Skindex-29 and SF-36 were consistent in that LCMN mainly reduced QoL from an emotional perspective. Conclusions: This research shows that LCMN has the strongest impact on patients’ emotional well-being but weakly influences the whole fettle of QoL. The gender, age and distribution patterns of lesions all have no direct effect on QoL, although a larger proportion of LCMNs probably insinuates worse QoL. Even though patients with LCMN show better QoL than those with other visible skin conditions, their general mental health still requires ample attention from surroundings and professional doctors.